2021
DOI: 10.1016/j.xpro.2021.100986
|View full text |Cite
|
Sign up to set email alerts
|

A proximity labeling protocol to probe proximity interactions in C. elegans

Abstract: Summary Enzyme-catalyzed proximity labeling (PL) has emerged as a critical approach for identifying protein-protein proximity interactions in cells; however, PL techniques were not historically practical in living multicellular organisms due to technical limitations. Here, we present a protocol for applying PL to living C. elegans using the biotin ligase mutant enzyme TurboID. We demonstrated PL in a tissue-specific and region-specific manner by focusing on non-centrosomal MTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…TurboID was found to provide tissue- and region-specific promiscuous biotinylation in Caenorhabditis elegans . Additionally by studying non-centromeric microtubule organizing centers (ncMTOCs) in intestinal cells, it was demonstrated that its tissue-specific and region-specific proximity markers make it suitable for in vivo targeted protein network analysis [ 133 ]. Artan et al optimized the proximity labeling approach using TurboID for Caenorhabditis elegans .…”
Section: Applications Of Biotin Ligase-based Proximity Marker Technologymentioning
confidence: 99%
“…TurboID was found to provide tissue- and region-specific promiscuous biotinylation in Caenorhabditis elegans . Additionally by studying non-centromeric microtubule organizing centers (ncMTOCs) in intestinal cells, it was demonstrated that its tissue-specific and region-specific proximity markers make it suitable for in vivo targeted protein network analysis [ 133 ]. Artan et al optimized the proximity labeling approach using TurboID for Caenorhabditis elegans .…”
Section: Applications Of Biotin Ligase-based Proximity Marker Technologymentioning
confidence: 99%
“…Proteomics based on proximity-labeling strategies using biotin ligases ( e.g. , BioID, TurboID-NES) are being increasingly used in in vitro and in vivo experimental contexts and in model systems ranging from plants ( 17 , 64 , 65 , 66 ), yeast ( 67 ), zebrafish ( 68 , 69 ), Drosophila ( 70 , 71 ), Caenorhabditis elegans ( 16 , 72 ), to mouse models ( 18 , 21 , 22 , 73 ). TurboID is one of the most efficient biotin ligases that can effectively label several proteins within a 10 nm labeling radius in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics based on proximity-labeling strategies using biotin ligases (e.g. BioID, TurboID-NES) are being increasingly used in in vitro and in vivo experimental contexts and in model systems ranging from plants 17,[51][52][53] , yeast 54 , zebrafish 55,56 , Drosophila 57,58 , C. elegans 16,59 , to mouse models 18,21,22,60 . TurboID is one of the most efficient biotin ligases that can effectively label several proteins within a 10nm labeling radius in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%